Pengaruh Kompensasi Dan Budaya Organisasi Terhadap Kinerja Karyawan PT AGS Di Kota Batam - Atmojo, Agus Sekti Susila (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2023)
This research to examine this research of compensation and organizational culture on employee performance of PT AGS. Data collection techniques in this study in used the questionnaires and literature study. Methods in this study using quantitative research techniques. The population and sample are PT AGS employees with 50 respondents. The results of this study indicate that, compensation has a positive and significant effect on employee performance. The value of 0,042 compensation significance is smaller than α = 0,05. The organizational culture has an effect on significance to the performance of PT AGS 0,003 less than α = 0,05. Based on Beta value, it is known that the dominant variable affecting employee performance is organizational culture of 0,512 (51,2%). Together, organizational compensation and culture have a positive and significant influence on PT AGS's performance. This decision is based on the level of significance of F value of 47,416 with a significance level of 0,000 smaller than α = 0,05